(untitled) (Research, Society and Development, 2022)
The social restriction due to the covid-19 pandemic caused the temporary suspension of face-to-face activities at universities, which may have increased the prevalence of symptoms of anxiety and depression due, among other factors, to changes in academic routines. This study aimed to estimate the prevalence of anxiety and depression symptoms and their association with academic routines of undergraduates during the covid-19 pandemic. It is a cross-sectional study carried out with baseline data from the PADu-COVID survey, conducted with 1,353 undergraduates from a Higher Education Institution. Data were collected through an online questionnaire. Outcomes were the presence of anxiety symptoms and symptoms of depression and the explanatory variables were academic routines. For bivariate and multivariate analysis Poisson regression was used, with a measure of association of Prevalence Ratio (PR), 95% confidence intervals (95%CI) and 5% statistical significance level. The prevalence of anxiety disorder and depression symptoms was 46.1% and 54.6%, respectively. The presence of one, two or more difficulties in dealing with the covid-19 pandemic was associated with symptoms of anxiety (PR 2.08 [CI95% 1.51-2.86]) and depression (PR 1.96 [CI95% 1.51-2.55]) and the decrease in study load was associated with symptoms of depression (PR 1.17 [95%CI 1.01-1.36]). Although necessary, the suspension of face-to-face activities seems to be related to the high prevalence found in students of symptoms of anxiety and depression disorders, and there is still dose-response relationship between the difficulties experienced by students and their mental health.